Uso de aplicativos computacionais e produto matricial: duas propostas de aplicação - Fogliarini Filha, Cláudia Brum de Oliveira (2015)
This work presents two educational proposals, directed to the high school, of matrix product aplication. The first proposal is made on geometric transformations (reflection, rotation, scale, shearing) with images of letters of the alphabet. It is divided into two parts: in the first, students need to make the product of matrices and the construction of the images, while in the second GeoGebra software is used to assist in the calculation and construction of the figures. The second proposal is about the projection of population growth through Leslie Model, using the Octave software as calculation tool. Before each proposal is provided the theory that supports geometric transformations as well the Leslie Model and several examples to clarify these definitions.